Survey on Micro-Raman Spectroscopy Data Analysis - Gomes, Elsa Ferreira; Ribeiro, Cristina Castro (Journal of Applied Nonlinear Dynamics, 2026)
The interest in the use of Raman spectroscopy in cancer diagnosis is due to its capability to unveil the evolution of the biochemical composition of tissue and cells throughout disease progression. Differences between Raman spectra of normal and malignant tissues and cells, both in vivo and in vitro, are being used as a method for the early detection of cancer. In this survey paper we review recently published works related to the analysis of data resulting from Raman spectroscopy. We structure our analysis according with the three steps of the process: data preprocessing, data reduction and data classification.